MENGOPTIMALKAN PEMAHAMAN KONSEP LARUTAN PENYANGGA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Misran Misran (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2010)
Abstract: This study was conducted to solve the students difficulties to understand buffer conceps by applying Cooperative learning model types of Student Teams Achievement Division (STAD) through class action research. The study was established in A’s eleventh class of 1’s Senior High School Labuan Amas Selatan. The first cycle was conducted in 3 actions and 1 action on the second cycle. The quantative and qualitative data got from this research including student’s achievement, student’s responses of the models and observational sheet. Research showed that there were no students pass the passing grade over on the pre test. While on the first cycle, there were 44,44% students pass the passing grade over. From the reflection of the first cycle it was found that students have difficulties both in solving buffer solution pH questions and explaining its use in dailiy life. Evaluation of the second cycle showed that 96,42% students passed the passing grade over. Obviously, STAD model is convinced to be able to increase student’s understanding in buffer solution concept. Affective assessment showed that 85,71% of students agree and extremely agree with the statement about STAD makes students understanding to the concept easier and improving student’s achievement, also they have a high interest to learn buffer solution concept. It was also found that there were 92,87% are active and very active in learning activities.Key words: cooperative learning model, buffer solution.